Calculating Multidimensional Deprivation Index for Women Living in Slums of Varanasi City - Jha, Darshan Kumar; Harshwardhan, Rahul; Tripathi, V. K. (National Geographical Journal of India, 2022)
This paper is an attempt to calculate Multidimensional Deprivation Index (MDI) for Women living in slums on the basis of versatile methodology of Multidimensional Poverty Index (MPI) which can be readily adjusted to incorporate alternative indicators, cut-offs and weights that might be appropriate in local contexts. Life is hard in slum where no basic facilities are available and it is much harder for women who are responsible for household, children and family members. Total ten indicators have been chosen from three sectors (health, economic and working status, value in family) to determine deprivation of female slum residents. The present study is based on Primary data which has been collected from six different slums of Varanasi city. The paper reveals that the more than 50 percent women living in six surveyed slums are multidimensionally deprived but spatial variation can be identified across all slums and across all indicators. The paper also identifies three different categories of slums on the basis of their deprivation score C.